(3OjhGf SHW GHf GdJYGhjPis - (3GHf GdJYGhjPj , CHh GdaJM eMeO Hf YHjOGddg Hf YHO Gddg, GHf GdJYGhjPj,J (B583 (3g` s ((3eMeO Hf CMeO Hf YHO Gddg s)
(3ChdgG (B:s
(3hChd GdehLhO efg bUjOI geRjI efgG (B: (3CJJee ai GdOfjG gOGI hai GdCNQi def Nd SYjg TaYGA s
(3BNQgG (B:s
(3dGHQMJ GdJgGfi hQHY CYOGFc GdZQGjG ced GdcJGH hGdMeO ddg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B260 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B278s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdCOHs